2022
DOI: 10.1111/bjd.20659
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis-related treatment exposure and hospitalization or in-hospital mortality due to COVID-19 during the first and second wave of the pandemic: cohort study of 1 326 312 patients in France

Abstract: Data availability statementWe used the French national health data system [Syst eme National des Donn ees de Sant e (SNDS)], which covers the entire French population (i.e. 67 million inhabitants in France).M.Z. and E.S. contributed equally to the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A French study assessed the outcome of COVID‐19 in adults with psoriasis from the national health insurance database and separately analysed the first and the second waves of the pandemic. 21 It found no difference in mortality between patients taking biologic vs. non‐biologic systemic drugs for both waves. They noted an increased risk of hospitalization for patients under non‐biologic systemic drugs during the first wave, without increased risk of mortality when compared to patients under biologic drugs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A French study assessed the outcome of COVID‐19 in adults with psoriasis from the national health insurance database and separately analysed the first and the second waves of the pandemic. 21 It found no difference in mortality between patients taking biologic vs. non‐biologic systemic drugs for both waves. They noted an increased risk of hospitalization for patients under non‐biologic systemic drugs during the first wave, without increased risk of mortality when compared to patients under biologic drugs.…”
Section: Discussionmentioning
confidence: 95%
“…A French study assessed the outcome of COVID‐19 in adults with psoriasis from the national health insurance database and separately analysed the first and the second waves of the pandemic 21 . It found no difference in mortality between patients taking biologic vs. non‐biologic systemic drugs for both waves.…”
Section: Discussionmentioning
confidence: 99%
“…The PMSI database contains details of all hospital admissions in France and hospital diagnoses according to the International Statistical Classification of Diseases and Related Health Problems (ICD‐10). These databases have been fully described elsewhere and are regularly used for the monitoring of drugs 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…TNF inhibitors plus MTX in psoriasis patients showed no difference in severe COVID-19 infection, but in certain cohorts [ 38 , 39 ], this treatment showed a decreased risk of COVID-19 infection and COVID-19-related mortality among IMID patients. Recent studies showed that non-biologics- or biologics-treated psoriasis patients with positive COVID-19 showed a decreased risk of severe COVID-19 infection [ 39 , 40 , 41 ]. These results suggest that IMIDs other than psoriasis treated with non-biologics may have an increased risk of severe COVID-19, while psoriasis patients are not at a higher risk of severe COVID-19 infection when treated either with biologics or non-biologics.…”
Section: Inflammation Exacerbates Covid-19 Infectionmentioning
confidence: 99%